DEVELOPMENT OF THE GUIDED INQUIRY STUDENT WORKSHEET FOR BIOLOGY GRADE 11TH SENIOR HIGH SCHOOL - Windiastuti, Erlin Permana; Suyono, Suyono; Kuntjoro, Sunu (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
The purpose of this study is produced Students? Worksheet (LKS) which valid, practice, and effective to support the learning biology materials using a guided inquiry model. The development of worksheets is using ADDIE (analyze, design, develop, implement, and evaluate) models and being implemented in XI Grade senior high of Trensains Tebuireng Jombang on odd semester of 2016/2017 academic year with the One-group pretest-posttest design. The validity of the worksheet is measured from consistency (construct validity) and relevant (content validity aspects) based on expert assessment with a minimum score of 2.60 (Valid). Practicality worksheet is measured from students? activities and Students? activities can be avowed good by minimum 65% of percentage. The effectiveness of the learning device is measured by its impact of the increasing of students? learning result in a pilot implementation or final implementation class as well as student?s response. Meanwhile, the learning device can be avowed effective if there are significant improvement scores of students? learning process in knowledge aspect. The responses of students are measured by the percentage of students? responses "Yes" in every aspect of the questionnaire with a minimum score of 61% of percentage. The validity and practicality of the data are analyzed descriptively while the increasing of learning cognitive aspects results are analyzed inferentially by using the paired t-test. Based on the data analysis results can be concluded that the development of learning device are valid, practical, and effective.